Disentangling the drivers of urban bird diversity in the non-breeding season : A general synthesis - Moreno-Contreras, Israel; Jokimäki, Jukka; Kaisanlahti-Jokimäki, Marja-Liisa; Leveau, Lucas M.; Suhonen, Jukka; Tobias, Joseph A.; Tryjanowski, Piotr (Wiley-Blackwell, 2025)
Current knowledge about the impacts of urbanisation on bird assemblages is based on evidence from studies partly or wholly undertaken in the breeding season. In comparison, the non-breeding season remains little studied, despite the fact that winter conditions at higher latitudes are changing more rapidly than other seasons. During the non-breeding season, cities may attract or retain bird species because they offer milder conditions or better feeding opportunities than surrounding habitats. However, the range of climatic, ecological and anthropogenic mechanisms shaping different facets of urban bird diversity in the non-breeding season are poorly understood. We explored these mechanisms using structural equation modelling to assess how urbanisation affects the taxonomic, phylogenetic and functional diversity of avian assemblages sampled worldwide in the non-breeding season. We found that minimum temperature, elevation, urban area and city age played a critical role in determining taxonomic diversity while a range of factors-including productivity, precipitation, elevation, distance to coasts and rivers, socio-economic (as a proxy of human facilitation) and road density-each contributed to patterns of phylogenetic and functional diversity. The structure and function of urban bird assemblages appear to be predominantly shaped by temperature, productivity and city age, with effects of these factors differing across seasons. Our results underline the importance of considering multiple hypotheses, including seasonal effects, when evaluating the impacts of urbanisation on biodiversity.